Supply Chain Management Information System Model for Agricultural Management in a Large Plots in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aimed to develop supply chain management information system model for agricultural management in a large plots in Thailand and an evaluation of the model. Samples are ten experts in the field of information system and supply chain. The data is analysed by means and standardized deviations. The research result shows that 1) the model consists of five elements namely main components, Farmer group ( Producers) , Field manager, Finished large plots. Consumers. the assessment of supply chain management information system model for agricultural management in a large plots in Thailand using Black-Box technique and the result of the assessment of supply chain management information system model for agricultural management in a large plots in Thailand shows the overall rating mean of 3.68 and standard deviation of 0.88, which means that the model is appropriate at the high level and can support sustainable Information system development.